Surgical Application of Human Amniotic Membrane and Amnion-Chorion Membrane in the Oral Cavity and Efficacy Evaluation: Corollary With Ophthalmological and Wound Healing Experiences - Odet, Stéphane; Louvrier, Aurélien; Meyer, Christophe; Nicolas, Francisco J.; Hofman, Nicola; Chatelain, Brice; Mauprivez, Cédric; Laurence, Sébastien; Kerdjoudj, Halima; Zwetyenga, Narcisse; Fricain, Jean-Christophe; Lafarge, Xavier; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Due to its intrinsic properties, there has been growing interest in human amniotic membrane (hAM) in recent years particularly for the treatment of ocular surface disorders and for wound healing. Herein, we investigate the potential use of hAM and amnion-chorion membrane (ACM) in oral surgery. Based on our analysis of the literature, it appears that their applications are very poorly defined. There are two options: implantation or use as a cover material graft. The oral cavity is submitted to various mechanical and biological stimulations that impair membrane stability and maintenance. Thus, some devices have been combined with the graft to secure its positioning and protect it in this location. This current opinion paper addresses in detail suitable procedures for hAM and ACM utilization in soft and hard tissue reconstruction in the oral cavity. We address their implantation and/or use as a covering, storage format, application side, size and number; multilayer use or folding, suture or use of additional protective covers, re-application and resorption/fate. We gathered evidence on pre- and post-surgical care and evaluation tools. Finally, we integrated ophthalmological and wound healing practices into the collected information. This review aims to help practitioners and researchers better understand the application of hAM and ACM in the oral cavity, a place less easily accessible than ocular or cutaneous surfaces. Additionally, it could be a useful reference in the generation of new ideas for the development of innovative protective covering, suturing or handling devices in this specific indication. Finally, this overview could be considered as a position paper to guide investigators to fulfil all the identified criteria in the future.